EFFECT OF JUSTICIA ADHATODA (MALABAR NUT) LEAF EXTRACT ON DRUG-INDUCED COAGULOPATHY IN MICE AND IN-VITRO PLATELET AGGREGATION OF HUMAN BLOOD - Zaffar, Sehrish; Malik, Mahwash; Rehan, Abdul Mudabbir; Rashid, Nazia; Chiragh, Sadia; Zaman, Kamran (Journal of Ayub Medical College Abbottabad, 2021)
Background: Justicia adhatoda is widely used in traditional medicine for treatment of menorrhagia, piles and bleeding disorders. Oral antiplatelet and anticoagulant drugs are routinely prescribed to patients with cardiovascular diseases. These drugs have one major adverse effect that they can cause spontaneous haemorrhage, which can be fatal. Development of a haemostatic agent can help in effective management of drug-induced haemorrhages. This study was devised to observe the effect of leaf extract of Justicia adhatoda on coagulation profile in mice and to evaluate its effect on in-vitro platelet aggregation. Methods: The study was divided into two parts. First part was designed to evaluate the effect of J. adhatoda leaf extract on coagulation parameters. Three drugs were used to induce coagulopathy viz., warfarin, aspirin and dabigatran. Bleeding time, platelet count, PT and APTT were estimated. Second part of this study was devised to observe the effect of J. adhatoda leaf extract on in vitro platelet aggregation of human. Percent aggregation was recorded by light transmission aggregometer for three minutes. Results Leaf extract of Justicia adhatoda decreased bleeding time from 6.1±2.36 minutes in normal control to 1.9±1.03 minutes in extract treated mice. There was no effect on the coagulation parameters. Platelet count increased significantly only in the aspirin treated group that received the extract to 540±46.8x103 /µl from 436.9±37.9x103 /µl of aspirin treated group. Platelet aggregation in vitro increased in a dose dependent manner. Conclusion: Justicia adhatoda leaf extract is effective in controlling excessive bleeding in vivo, in mice with acquired platelet defect produced by aspirin. This haemostatic effect is probably due to increased platelet aggregation as indicated by the in vitro results. Keywords: Haemostasis; Justicia adhatoda; platelet aggregation; coagulation; coagulopathy